Top notch Fundamentals : - Saslow, Joan M (Longman, 2006)
Top Notch provides students an opportunity to confirm their own progress at the end of every easy-to-teach two-page lesson. Features of Top Notch Fundamentals *Essential model conversations that make key social language unforgettable and easy to personalize *Intensive vocabulary development with active recycling *Complete grammar support--extended by a bound-in Vocabulary Booster *"Top Notch Interactions"--unique step-by-step discussion builders that guarantee success for all learners *Thorough attention to pronunciation *A wide array of learning strategies and activities that promote critical thinking *Authentic and refreshing content that connects students to the real world